(3GdeLQHGJs - (3RgQ Hf YHO Gdedc Hf eMeO Hf RgQ GdGTHjdj, CHh GdYdGA,J (B525 (3g` s
(3ChdgG (B:s
(3bGd GHhGdYdGA Hf RgQ QMeI Gddg Ydjg jNGWH EHfg JPcQ, hGddg JYGdi jUMHc GdSdGeI , eG CdbjJg Edjc hgh Cf eYXe CWHGA ReGffG gPG dGjejdhf ai QhjJge VO GdLgI GdJi eGd GdeRGL EdjgG HbOQ Pdc Gdejd s
(3BNQgG (B:s
(3hbGd fTGQI NTH GdUfhHQ hbdbOjS , ef cd hGMO LRA, jNdWGf hjJHNQ HgeG ajbJd GdHb Ef TGA Gddg JYGdi s
(3hGfXQ efg fSNI CNQi HYfhGf (B: (3GdJPcQI Qbe (B"638"s
(3ChQGbgG oeVWQHIs
(3hHChQGbgG ahGFO WHjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs